2016
DOI: 10.18632/oncotarget.11640
|View full text |Cite
|
Sign up to set email alerts
|

DNA methylation array analysis identifies breast cancer associated RPTOR, MGRN1 and RAPSN hypomethylation in peripheral blood DNA

Abstract: DNA methylation changes in peripheral blood DNA have been shown to be associated with solid tumors. We sought to identify methylation alterations in whole blood DNA that are associated with breast cancer (BC). Epigenome-wide DNA methylation profiling on blood DNA from BC cases and healthy controls was performed by applying Infinium HumanMethylation450K BeadChips. Promising CpG sites were selected and validated in three independent larger sample cohorts via MassARRAY EpiTyper assays. CpG sites located in three … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
36
1

Year Published

2016
2016
2022
2022

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 31 publications
(39 citation statements)
references
References 52 publications
(64 reference statements)
2
36
1
Order By: Relevance
“…Of the included 33 studies, 25 studies applied a gene-specific approach and reported 70 methylation markers, and eight studies (20, 22, 23, 27-29, 35, 46) identified methylation markers using array-based technologies (Illumina 27K or 450K beadchip) and reported 285 differentially methylated CpG sites. Among these 285 CpG sites, nine CpG sites including C7orf50-cg03916490, GREB1-cg18584561, HYAL2-cg27091787, MGRN1-cg00736299, RPTOR-cg06418238, RAPSN-cg27466532, PNKD-cg01741999, TMC3-cg27639199, and S100P-cg22266967 were further confirmed in independent samples from the same studies (20,22,23,27). We summarized these nine CpG sites together with the 70 gene-specific markers in Table 1 and present the other 276 CpG sites in Supplementary Table S2.…”
Section: Overview Of Whole-blood Based Dna Methylation Markersmentioning
confidence: 77%
See 3 more Smart Citations
“…Of the included 33 studies, 25 studies applied a gene-specific approach and reported 70 methylation markers, and eight studies (20, 22, 23, 27-29, 35, 46) identified methylation markers using array-based technologies (Illumina 27K or 450K beadchip) and reported 285 differentially methylated CpG sites. Among these 285 CpG sites, nine CpG sites including C7orf50-cg03916490, GREB1-cg18584561, HYAL2-cg27091787, MGRN1-cg00736299, RPTOR-cg06418238, RAPSN-cg27466532, PNKD-cg01741999, TMC3-cg27639199, and S100P-cg22266967 were further confirmed in independent samples from the same studies (20,22,23,27). We summarized these nine CpG sites together with the 70 gene-specific markers in Table 1 and present the other 276 CpG sites in Supplementary Table S2.…”
Section: Overview Of Whole-blood Based Dna Methylation Markersmentioning
confidence: 77%
“…The study characteristics are provided in Supplementary Table S1. Of the 33 identified studies, 16 were carried out in Europe [five studies from Germany (20,22,23,26,35) and five studies from the United Kingdom (16,18,28,36,37)], nine studies were from Asian countries (17,19,21,33,(38)(39)(40)(41)(42) and three studies were from the United States (29,43,44). The majority of included studies recruited breast cancer cases from clinical settings and one study (45) was restricted to cases with family history of breast cancer.…”
Section: Study Characteristicsmentioning
confidence: 99%
See 2 more Smart Citations
“…This specific CpG has been previously presented as a marker to differentiate between different medulloblastoma subtypes [67]. Another study has also indicated that the decrease in methylation in RPTOR measured in peripheral blood may be a biomarker for breast cancer, although this failed replication in a follow-up study [68, 69]. Similar to REC8 , there was more negative change in β-value from Year 1 to 6 in individuals closer to receiving a cancer diagnosis.…”
Section: Discussionmentioning
confidence: 90%